Optimized peripheral blood progenitor cell mobilization for autologous hematopoietic cell transplantation in children with high‐risk and refractory malignancies. (20th October 2019) - Furlong, Eliska; Jensen, Jesper; Woodard, Mark; Griffiths, Katherine; Knight, Geoff; Sturm, Marian; Kerr, Fiona; Gough, Hazel; Bear, Natasha; Carter, Tina L.; Cole, Catherine H.; Kotecha, Rishi S.; et al.
Abstract: Background: Autologous hematopoietic stem cell transplantation (aHSCT) using hematopoietic progenitor cells (HPCs) has become an important therapeutic modality for patients with high‐risk malignancies. Current literature on standardized method for HPC apheresis in children is sparse and failure rate reported as high as 30%. Patients/Methods: A retrospective study of 125 pediatric patients with high‐risk malignancies undergoing aHSCT in Western Australia between 1997 and 2016 was conducted. Results: Mobilization was achieved by means of chemotherapy and granulocyte colony‐stimulating factor (G‐CSF). Patients underwent apheresis the day after CD34 + counts reached ≥20/µL and an additional dose of G‐CSF. Peripheral arterial and intravenous lines were inserted in pediatric intensive care unit under local anesthetic and/or sedation, omitting the need for general anesthesia as well as facilitating an uninterrupted apheresis flow. Larger apheresis total blood volumes were processed in patients weighing ≤20 kg. The minimal dose of ≥2 × 10 6 CD34 + cells/kg was successfully collected in 98.4% of all patients. The optimal dose of 3‐5 × 10 6 CD34 + cells/kg was collected in 96% of patients scheduled for a single aHSCT, 87.5% for tandem, and 100% for triple aHSCT. All HPC collections were completed in one apheresis session. Mobilization after ≤3 chemotherapy cycles and cycles including cyclophosphamide resulted in a significantly higher yield of CD34 + cells. Conclusion: Our approach to HPC mobilization by means of chemotherapy and single myeloid growth factor combined with optimal collection timing facilitated by continuous apheresis flow resulted in highly effective HPC harvest in children and adolescents with high‐risk cancers.